Critical attributes on supply chain strategy implementation: case study in Europe and Asia - Sillanpää, Ilkka; Malek, Nurul Aida binti Abdul; Takala, Josu (Polish Association for Production Management, 2013)
This case study research aims to compare the performance of the implementation of supply chain management (SCM) strategies within Asian and European Companies. The case study measures company’s opinions of supply chain strategy implementation through utilization of Sense and Response methodology. Critical Factor Index (CFI), Balanced Critical Factor Index (BCFI) and Scaled Critical Factor Index (SCFI) are used in this study to represent the result of comparison between European and Asian companies. From the analysis of comparison of all Sense and Response models, it can be concluded that there are differences and similarities of critical attributes that affecting supply chain strategy implementation in Asian and European companies. There are two attributes that have consistent trend for both regions; innovation and organization structure.In this research the analysis of supply chain strategy implementation was made for the needs of manufacturing industry. Suggestions for future research are multiple case studies in different industry areas in global business environment.The results provide a guideline to the company to measure the right attributes for making the right decision in a dynamic environment. It also provides good knowledge for companies to implement supply chain strategies, the main approaches to implement it and the main challenges in supply chain strategy implementation. Supply chain strategy implementation was analyzed in the European and Asian companies. This research shows that there are several developing areas for companies when implementing supply chain strategies.
Keywords: supply chain management; sense and respond; strategy implementation; fi=Tuotantotalous|en=Industrial Management|